Formulation and Evaluation of Sustained-Release Microspheres for Anti-Inflammatory Drug Delivery - Pandey, Prateek; Mishra, Amit Kumar; priyanka, kondampalli; Bisht, Aknasha; Arora, Rimjhim; Dhalpe, Shekhar; Gangwar, Poonam; Khatoon, Shabana (Journal of Neonatal Surgery, 2025)
Sustained-release microspheres have emerged as an innovative drug delivery system tailored to enhance the therapeutic efficacy and reduce side effects of anti-inflammatory drugs. This study focuses on the formulation and comprehensive evaluation of sustained-release microspheres designed for effective anti-inflammatory drug delivery. Utilizing polymers such as poly(lactic-co-glycolic acid) (PLGA), chitosan, and ethylcellulose as carriers, various preparation techniques including emulsion solvent evaporation, microfluidics, and spray drying were employed to encapsulate anti-inflammatory agents. The formulated microspheres were characterized for particle size, morphology, encapsulation efficiency, and in vitro drug release profiles. Results demonstrated uniform particle size distribution, high drug entrapment efficiency, and a controlled, prolonged drug release over targeted durations up to several days, depending on formulation parameters. The sustained-release formulation effectively mitigated the initial burst effect and maintained therapeutic drug concentrations, potentially enhancing patient compliance by reducing dosing frequency. Further, in vitro and in vivo evaluations suggest these microspheres hold promise in minimizing gastrointestinal irritation commonly associated with conventional therapies. This research provides a systematic understanding of the fabrication parameters and evaluation methodologies critical for optimizing sustained-release microspheres, thereby advancing their application in anti-inflammatory drug delivery and improving clinical outcomes